Kajian Aerodinamika Pada Model Kendaraan dengan Penerapan Kontrol Aktif Suction - Rustan Tarakka; Nasaruddin Salam; Jalaluddin Jalaluddin; Wawan Rauf; Muhammad Ihsan (Department of Mechanical Engineering, Universitas Andalas, 2021)
As the air flow reaches the rear part of the vehicle the flow will undergo separation generated by friction and fluid viscosity, and creating wake, considerably large turbulent area with low pressure at the rear of the vehicle which results in pressure drag which can reduce vehicle performance. The research was carried out with a computational and experimental approach. The test model used in this study is a model of a family van model which is a modification of the Ahmed body model. The rear part of the vehicle model is equipped with an active control feature in the form of a suction with a slant angle (α) of 35°. The upstream speed and suction speed are 11.1 m/s and 0.5 m/s, respectively. The results obtained indicate that the application of active suction control is able to reduce wake formation and delay flow separation compared to the uncontrolled model, and is able to increase the minimum pressure coefficient on the rear wall of the vehicle model with an increase of 41.49%, and is able to reduce the drag coefficient by 11.0260% for the approach. computation and 11.0080% for the experimental approach.